Study to assess the knowledge, attitude and practice of Kangaroo mother care among post-natal mothers in a tertiary care centre of Mangalore, Karnataka, India - Gulati, Paras; Bhat, Sinchana; Maben, Roshan; T. Soans, Santhosh (International Journal of Contemporary Pediatrics, 2019)
Background: Kangaroo mother care (KMC) is a practical low-cost intervention which is very cost effective in developing countries for babies weighing less than 2500g. This study aimed to evaluate the knowledge, attitude and practice of post-natal mothers of LBW babies after giving a teaching session by trained personnel in a tertiary care center in Karnataka. Methods: A cross sectional descriptive study of 90 mothers whose neonates were weighing less than 2.5kg from May to October 2018.Mothers were interviewed at enrolment and were assessed about their knowledge and were oriented on its practice. Results: At recruitment (95.5%) mothers did not know about KMC.80% of mothers followed in first sitting and 86.6% of the mothers felt photo exhibition was better than verbal.96.6% of mothers thought KMC is beneficial and it was believed that other family members can even provide KMC. Conclusions: Maternal knowledge was low before now they are happily practicing KMC in hospital and thereafter at home.